Geometry of highly inclined protoplanetary disks - Zakhozhay, O.V.; del Burgo, C.; Zakhozhay, V.A. (Advances in Astronomy and Space Physics, 2015)
We present a geometric model for the modelling of spectral energy distribution of inclined protoplanetary disks. We investigate peculiarities in the geometry of nearly edge-on disks with an inner hole and a central object. In the investigation we consider two cases: that of geometrically thin disks (where the star is larger than the rim of the inner edge of the disk) and that of eometrically thick disks (when the star is smaller than the inner rim of the disk). Our model is appropriate for modelling substellar objects with primordial gas-rich disks, as activity (such as accretion or outflows) in such disks has low amplitude and can be ignored even when modelling early evolution stages. Furthermore, it can also be used to model any symmetric system with a disk and a spherical central body (star, brown dwarf or giant planet).